Can Thyroid Ultrasonography Predict Substernal Extension or Tracheal Compression in Goiters?. Issue 4 (November 2018) - Ziai, Hedyeh; Lebo, Nicole L.; Kielar, Ania Z.; Odell, Michael J.
Purpose: To determine whether an ultrasonography (US)-defined thyroid volume can accurately predict substernal extension or tracheal narrowing. Methods: After research ethics approval, we identified patients with thyroid nodules investigated with both US and computed tomography (CT). Reviewers assigned scores for both substernal extension and tracheal compression on CT using pre-established classification systems. Statistical analysis with receiver operating characteristic curve analysis was performed to find the US-determined thyroid volume thresholds that correlated with each substernal extension and tracheal compression. Results: This study included 120 patients (mean age 63.4 years; SD ± 15.9; 67% female). Thirty-five patients (29%) had substernal extension. The mean US total thyroid gland volume in patients with and without substernal extension were 92.4 and 37.6 cm 3, respectively ( P < .001). 86% of patients with substernal extension had tracheal narrowing vs. 27% of patients without substernal extension ( P < .0001). A cutoff dominant gland volume of ≥37.5 cm 3 showed 83% sensitivity and 79% specificity for substernal extension (area under the curve [AUC] = 0.84). A total thyroid gland volume threshold of ≥37.8 cm 3 showed 89% sensitivity and 87% specificity for any degree of tracheal narrowing (AUC = 0.90). Conclusions: This study suggests that US volumes may be used as a predictor to identify those patients with thyroid enlargement who are most at risk of substernal extension and tracheal compression and who may benefit from preoperative CT imaging for optimal surgical and anesthetic planning.